Review of the implementation of road preservation and road shoulder widening on SP. Lempake - SP3. Sambera - Santan Project - Pratiwi, Dheka Shara; Albar, Albar (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2023)
The main road is a crucial transportation facility that plays a significant role in various community activities in a region, both in urban and rural areas. The total length of this road improvement project is 52.71 km. The enhancement of the SP.Lempake-SP3.Sambera-Santan Road is expected to help improve services and facilitate upgrading road facilities for transportation purposes, benefiting the local community and existing industries. This study utilizes the participatory observation method. Participatory observation is a data collection method that directly involves a researcher in the research location, allowing them to participate in observational activities. The purpose of observation here is for the researcher to be directly engaged in supervising the road preservation and widening project of the SP. Lempake-SP3.Sambera-Santan road. Data collection involves primary data, including on-site observation methods, interviews, documentation, and secondary data used in this report, such as plan drawings, time schedules, and organizational structure. The widening of the SP.Lempake - SP3. Sambera-Santan road consists of several tasks, including preparatory work, excavation, spreading and compacting of Class A aggregates, structural work, and the final finishing work. Challenges faced during the project include weather conditions (rain) and material depletion.